Positive Devience and Early Life Nutrition Based on Local Wisdom for Pregnant Women with The Nutrional Status of Children Aged 0-5 Years with Covid-19 Case - Ana Samiatul Milah; Ade Zaqiah; Mohammad Yudio Fuad (International Journal of Sustainable Applied Sciences, 2023)
The significant role of a mother is primarily evident from the birth of her baby. So that the pattern of nutritional intake of pregnant women can be in line with health standards. A mother who is pregnant in a household that is also part of the family is no longer an adult, but a mother must be seen as a complete and unique individual whom she has a dual role in terms of nutritional intake at the time of her pregnancy. A mother has special and greater needs that are different from the ones of ordinary adults. An adequate and balanced intake of nutritional needs is very important for the pregnancy to prevent iron deficiency and essential fatty acids in newborn infants and toddlers. The pattern of nutritional intake plays an important role in providing standard nutritional intake (Needs: Carbohydrates, Proteins, Vitamins, Minerals, Fats). Coronavirus diseases 2019 or what we usually short for covid-19 is now a problem in Indonesia and even in the world, especially after death cases in a short time. Knowledge about outbreaks and health protocol rules on adapting normal habits in the community is still very lacking. Corona Virus Disease 2019 is a type of virus identified as the cause of disease in the respiratory tract. Transmission of Corona Virus Disease 2019 or Covid-19 still occurs over the globe. The World Health Organization (WHO) recommends the program to reduce the incidence of Covid-19 transmission. The main causes of death in children under five years during pregnancy in developing countries, based on the death related to malnutrition by 35%, namely pneumonia 20%, diarrhoea 15%, dengue 11%, perinatal 23%, other 22%, meals 5% and HIV/AIDS 4%. The research carried out in Baregbeg Village, Baregbeg District, Ciamis Regency in 2022.